2007
DOI: 10.1002/chem.200600792
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Activation by Surface Excess Electrons: An EPR Study of the CO2 Radical Ion Adsorbed on the Surface of MgO

Abstract: The CO2- radical anion has been generated at the surface of MgO by direct electron transfer from surface trapped excess electrons and characterized by electron paramagnetic resonance spectroscopy. Both 13C and 17O hyperfine structures have been resolved for the first time, leading to a detailed mapping of the unpaired electron spin density distribution over the entire radical anion. The magnetic equivalence of the two O nuclei has been ascertained allowing a side-on adsorption structure at low-coordinate Mg2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 33 publications
4
47
1
Order By: Relevance
“…The model proposed by Pong et al (15), based on asymmetric vibrational bands of a strongly interacting CO 2 /cyclobutadiene system in which the CO 2 molecule bends in either a perpendicular or parallel manner relative to the plane of the cyclobutadiene, can unambiguously correlate with our experimental structure. Finally, under photoexcitation conditions, the formation of a bent CO 2 radical anion (12,13) in interaction with the Me 2 CBD S radical cation via strong ionic bonds-more in line with the observed C2-C3 and C6-O1 distances-seems reasonable because the host matrix is ionic and polar. We agree with Scheschkewitz (2) and Alabugin et al Regarding the Me 2 CBD R rectangular geometry, the CO 2 is perpendicularly oriented with respect to the C 3 C 4 C 5 C 6 ring of Me 2 CBD S , and a proposed Dewar-b-lactone enantiomer Me 2 CBD R (2) does not fit with the distorted structure as presented in Fig.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The model proposed by Pong et al (15), based on asymmetric vibrational bands of a strongly interacting CO 2 /cyclobutadiene system in which the CO 2 molecule bends in either a perpendicular or parallel manner relative to the plane of the cyclobutadiene, can unambiguously correlate with our experimental structure. Finally, under photoexcitation conditions, the formation of a bent CO 2 radical anion (12,13) in interaction with the Me 2 CBD S radical cation via strong ionic bonds-more in line with the observed C2-C3 and C6-O1 distances-seems reasonable because the host matrix is ionic and polar. We agree with Scheschkewitz (2) and Alabugin et al Regarding the Me 2 CBD R rectangular geometry, the CO 2 is perpendicularly oriented with respect to the C 3 C 4 C 5 C 6 ring of Me 2 CBD S , and a proposed Dewar-b-lactone enantiomer Me 2 CBD R (2) does not fit with the distorted structure as presented in Fig.…”
mentioning
confidence: 52%
“…The CO 2 -IV phase structure confirms that at high pressure (a scenario not very different from confined conditions), CO 2 molecules are nonlinear (9). Interactions with metals (10) or metal ions (11), or ultraviolet photoreactions (12)(13)(14) can also produce bent states of CO 2 . Third, Maier et al (15) and Pong et al (16) independently showed the tendency of cyclobutadiene to undergo strong association with ligands (including CO 2 ) constrained to remain in close proximity by a solid matrix.…”
mentioning
confidence: 99%
“…The ultra‐thin structure can expose more active sites on the surface; the surface metal atoms may have lower coordination numbers compared with the metal atoms inside the structure. Previous research has confirmed that a low coordination surface metal cation may serve as an adsorption site . Fe nanoparticles (NPs) are not observed in the HRTEM image (Figure a, S5, and S6), so it can be roughly inferred that the active site Fe–N 4 is dispersed at the atomic‐level.…”
Section: Resultsmentioning
confidence: 99%
“…3) of CO 2 with a nucleophilic oxygen atom, an electrophilic carbon atom and a π system provides the chemist with many options. Likewise, a rich coordination chemistry to metal centres has been reported for CO 2 [56]. A forthcoming path is the reaction of CO 2 to form energy-rich intermediates that can subsequently transfer the CO 2 molecule to target substrates [7].…”
mentioning
confidence: 99%
“…Threefold reactivity of carbon dioxide and examples for different activation modes for CO 2 involving metal centres in homogeneous and heterogeneous catalysts [56]. …”
mentioning
confidence: 99%